PENGARUH PROFESIONALITAS GURU PENDIDIKAN AGAMA ISLAM TERHADAP RELIGIUSITAS (PRAKTEK IBADAH INDIVIDU) PESERTA DIDIK DI KELAS X DAN XI SMK INFORMATIKA SUKMA MANDIRI CILEGON - Ahmad Jauharuddin; Siti Rohmah (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2023)
Professionalism is a condition that shows the degree of professionalism of a person to carry out their duties. This relates to academic qualifications, and teacher competence in accordance with the fields. Religiosity is a system of worship and doctrine that exists in a group. Students are doctrine at school they have good religiosity. Religiosity in the school environment is reflected in the practice of prayer and other services. However, the reality is that not all students carry out their worship properly. Such as ignoring prayer times, lack of enthusiasm in worship practices, and so on. Thus, a professional teacher has a very important role in increasing the religiosity of their students, and people who are faithful and pious. This study uses a quantitative approach. Data collection techniques were carried out by observation and questionnaires. The sample was 61 students. This study uses regression analysis and the results show that the professionalism of Islamic Religious Education teachers (X) has a significant effect on the religiosity (individual worship practice) of students in grades X and XI (Y), obtained Fcount (14.406) > Ftable (4.00) so that Ho is rejected/ Ha is accepted. With a coefficient of determination (R Square) of 0.196. This means that the effect of Islamic Religious Education Teacher Professionalism (X) on Religiosity (Individual Worship Practice) of grades X and XI (Y) students is 19.6%, and the remaining 80.4% is affected by other factors.